Soil Phosphorus Fractions After Long-Term Fertilizer Placement in Different Kansas Soils - M. J. Coelho; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2020)
Phosphorus (P) fertilizer placement can affect the long-term dynamics and forms of P, and the overall soil P pools. These changes can vary by soil type, and affect P uptake and use efficiency by crops. The objective of this study was to evaluate the changes in the labile P fractions in three Kansas soil types under P fertilizer placements (broadcast versus deep band) after ten years of crop rotation. Three field studies were conducted at Scandia, Ottawa, and Manhattan. Three treatments were evaluated: 1) a control with no P fertilizer application and two fertilizer treatments (80 lb P2O5/a); 2) surface broadcast; and 3) deep band at approximately 4–6 in. depth. All treatments received strip-tillage. After ten years, soil samples were collected from the row, and between the row at two sampling depths (0–3 and 3–6 inches) and soil P pools (inorganic and organic P labile) were measured. Significant changes in soil labile P pools for treatments compared to control were observed due to the long-term effect of P fertilizer placement. The broadcast P fertilizer placement increased the total labile (PtLP) and inorganic labile P (PiLP) in the soil surface (0–3 in.) and deep band in the subsoil (3–6 in.) at all sites studied. However, the highest amount of organic labile P (PoLP) was observed for the control broadcast treatments in the subsoil (3–6 in.) at the Scandia site. The total labile P was affected by maximum P adsorption capacity (MPAC) and P fertilizer placement.
Keywords: Soil fertility; phosphorus; fertilizer; corn; soybean